Factors contributing to frequent attendance to the emergency department of a remote Northern Territory hospital. Issue 3 (15th February 2016) - Quilty, Simon; Shannon, Geordan; Yao, Anthony; Sargent, William; McVeigh, Michael F
Abstract: Objectives: To determine the clinical and environmental variables associated with frequent presentations by adult patients to a remote Australian hospital emergency department (ED) for reasons other than chronic health conditions. Design: Unmatched case–control study of all adult patients attending Katherine Hospital ED between 1 January and 31 December 2012. Participants: Cases were defined as frequent attenders (FAs) without a chronic health condition who presented to the ED six or more times during the 12‐month period. A single presentation was randomly selected for data collection. Controls were patients who presented on only one occasion. Outcome measures: Basic demographic data were collected, including clinical outcomes, Indigenous status, living arrangements, and whether alcohol and violence contributed to the presentation. Environmental variables were extracted from the Bureau of Meteorology database and mapped to each presentation. Results: FAs were much more likely to be homeless (odds ratio [OR], 16.4; P < 0.001) and to be Aboriginal (OR, 2.16; P < 0.001); alcohol as a contributing factor was also more likely (OR, 2.77; P = 0.001). FAs were more likely to present in hotter, wetter weather, although the association was statistically weak. Clinical presentations by cases and controls were similar; the annual death rates for both groups were high (3.6% and 1.5%, respectively). Conclusions: There was a strong association between FA and Aboriginal status, homelessness and the involvement of alcohol, but alcohol was more likely to contribute to presentation by non‐Aboriginal FAs who had stable living conditions. FAs and non‐FAs had similar needs for emergency medical care, with strikingly higher death rates than the national average in both groups. As a result of this study, Katherine Hospital has initiated a Frequent Attender Pathway that automatically triggers a dedicated ED service for those at greatest clinical risk. Homelessness is a serious problem in the Northern Territory, and is associated with poor health outcomes.